Self-esteem and unconditional acceptance of oneself, in HIV positive people - Sandu, Mihaela Luminita; Calin, Mariana Floricica; Fusea, Mariana Violeta (Technium Social Sciences Journal, 2023)
The present work entitled "Self-esteem and unconditional acceptance of oneself, in seropositive people", highlights the problem of real states, which seropositive people face, to situations and intercessions related to self-esteem. This followed the behavior of HIV positive people, attitudes towards other people or vis-à-vis their own lives. Self-esteem is an element of the self and refers to affective living, to the emotions that the individual experiences when referring to himself. It is a make-up of the cognitive scheme relating to oneself. The idea that self-esteem is one of the factors that are associated with mental health is an integral part of psychology. The level of self can influence the habits and manifestations of the individual, so in the case of a low level the person gives up a succession of attractive goals, such as establishing close interpersonal relationships, choosing desired professions or living a pleasant life full of accomplishments and satisfactions. A low self-esteem can turn a healthy and intelligent person into a powerless person. The transition from a healthy and high self-esteem to a low self-esteem can be achieved by triggering strong mechanisms, in critical situations such as in the case of the presented theme, the establishment of a positive serodiagnostic. This fact causes the person to adopt ub devaluation behavior. The work being focused on self-esteem is designed so as to highlight the main aspects of the subject, so it is structured on chapters as follows in those presented below.